2011
DOI: 10.1021/np2003066
|View full text |Cite
|
Sign up to set email alerts
|

Berkeleyones and Related Meroterpenes from a Deep Water Acid Mine Waste Fungus That Inhibit the Production of Interleukin 1-β from Induced Inflammasomes

Abstract: The Berkeley Pit, an acid mine waste lake, is a source of extremophilic microorganisms that produce interesting bioactive compounds. We have previously reported the isolation of berkeleydione 1, berkeleytrione 2, the berkeleyacetals and the berkeleyamides from the Pit Lake fungus Penicillium rubrum. In this paper we report the isolation and characterization of berkeleyones A-C (4, 5 and 7) as well as previously described preaustinoid A (3) and A1(6) from this same fungus. These compounds were evaluated as inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 25 publications
1
56
1
Order By: Relevance
“…The COSY and HMBC data associated with the D and E rings of 1 are present in the NMR spectra of 2 ( Figure 2), and the 1 H and 13 C NMR spectroscopic data of these two rings of 2 are comparable to those of 1 (Table 1), which provides ample evi- dence of the D and E rings and discloses the location of the last oxygen atom. Besides, much of the NMR spectroscopic data associated with the B ring and its isopropenyl and propionic acid side-chains of berkeleyone C (8) [10] are also present in the Figure 2). These data provide sufficient evidence for the ring B and its adjacently positioned isopropenyl and propionic acid substituent groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The COSY and HMBC data associated with the D and E rings of 1 are present in the NMR spectra of 2 ( Figure 2), and the 1 H and 13 C NMR spectroscopic data of these two rings of 2 are comparable to those of 1 (Table 1), which provides ample evi- dence of the D and E rings and discloses the location of the last oxygen atom. Besides, much of the NMR spectroscopic data associated with the B ring and its isopropenyl and propionic acid side-chains of berkeleyone C (8) [10] are also present in the Figure 2). These data provide sufficient evidence for the ring B and its adjacently positioned isopropenyl and propionic acid substituent groups.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the spectroscopic and specific rotation data with literature values, the remaining four known compounds were identified as preaustinoid A1 (7), [9] berkeleyone C (8), [10] berkeleyacetal A (9), [11] and preaustinoid A3 (10) [12] (see Tables S9 and S10 in the Supporting Information), among which only the absolute configuration of preaustinoid A1 (7) was reported previously as shown. [19] In this work, we also clarified the absolute configurations of compounds 8-10.…”
Section: Hr-esi-ms Analysis Of 1-methoxy-hydropreaustinoid A1 (3) Yiementioning
confidence: 85%
See 2 more Smart Citations
“…An umber of meroterpenoids containing ab ridged [7.3.1.0 2,7 ] tricyclics ystem and their derivatives have been isolated and characterized as fungal metabolites since the discovery of neoaustin in 1994 ( Figure 1). [1,2] Although some of these natural products have been reported to display remarkable biological activities (e.g.,i nhibition of caspase-1), studies toward the synthesis of these meroterpenoids have not been reported to date.…”
mentioning
confidence: 99%